MOTIVASI TIONGKOK MENDIRIKAN AIR DEFENSE IDENTIFICATION ZONE (ADIZ) DI WILAYAH LAUT CINA TIMUR - Lubis, Khairunnisa Jani; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains Tiongkok’s motive established an Air Defense Identification Zone (ADIZ) in the East China Sea. The Ministry of National Defense of the People’s Republic of China on 23rd November 2013 declared an Air Defense Identification Zone (ADIZ) in the East China Sea. This new ADIZ covers the Senkaku Islands, which under a territory dispute between Tiongkok and Japan.This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case is library research in the form of journals, books, thesis, reports, working papers, magazine, and website to explain Tiongkok’s motive on establishing its ADIZ. The theoretical framework applied in this research are realism perspective, foreign policy strategy theory from John P. Lovell, national interests concept from Hans J. Morgenthau and threats concept from Barry Buzan.The research shows that Tiongkok’s motive by established an ADIZ was not genuinely to defend its sovereignty and the security of Chinese territory and airspace, but the ADIZ is an expansion of Tiongkok’s attempt to exert legal and administrative control over the Senkaku Islands. This is also a counter-measure for Japan’s nationalization over the islands. Tiongkok will defend any sovereignty that it’s has because Senkaku Island is a core interest for Tiongkok.Keywords: ADIZ, foreign policy, national interest, Tiongkok, Senkaku/Diaoyu, territorial dispute. East China Sea.